The role of mitochondria in ageing - Pollard, Amelia K. (2017)
Cognitive decline coupled with functional loss of skeletal muscle strength is a quietly devastating reality for long-lived populations. Ageing is a complex process resulting in the progressive deterioration of biological functions, however the exact mechanisms of ageing are currently unclear. Mitochondrial dysfunction is a characteristic feature of ageing and age-related disease. This thesis explored the age-related changes to biochemical profile of the mitochondrion.